2008
DOI: 10.1007/s12288-008-0030-y
|View full text |Cite
|
Sign up to set email alerts
|

Crystal storing histiocytosis: a rare presentation of plasma cell myeloma

Abstract: Crystal storing histiocytosis (CSH) is a very rare association with plasma cell dyscrasias. It is presumed to be an intra-lysosomal accumulation of the secreted paraprotein aggregated into crystals and is associated with presence of variable numbers of histiocyte-like cells with phagocytosed crystalline inclusions in the bone marrow and other extramedullary sites Herein we report a case of multiple myeloma associated with CSH with a rapidly downhill clinical course. There was diagnostic confusion at the outset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
(5 reference statements)
1
0
0
Order By: Relevance
“…The mutation leads to a block in the secretion of the kappa light chains and resultant accumulation within plasma cells. Similar cases of crystal‐storing histiocytosis associated with plasma cell dyscrasias have been reported previously, and it has been observed that these patients have a rapid clinical course .…”
Section: Discussionsupporting
confidence: 85%
“…The mutation leads to a block in the secretion of the kappa light chains and resultant accumulation within plasma cells. Similar cases of crystal‐storing histiocytosis associated with plasma cell dyscrasias have been reported previously, and it has been observed that these patients have a rapid clinical course .…”
Section: Discussionsupporting
confidence: 85%